Defining Clinical and Microbiological Nonresponse in Ventilator-Associated Pneumonia - Ceccato, Adrian; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2022)
Ventilator-associated pneumonia (VAP) is a severe complication of mechanical ventilation, with mortality reduced most effectively by adequate early antibiotic treatment. The clinical and microbiologic response can be assessed easily from 72 hours after starting antibiotic treatment. Evidence of nonresponse is based on several factors: (1) lack of clinical improvement, (2) radiographic progression, (3) an impaired Sequential Organ Failure Assessment (SOFA) score, (4) no improvement by days 3 to 5 on the Clinical Pulmonary Infection Score (CPIS), (5) no decreased in biomarkers on day 3, and (6) isolation of a new pathogen on day 3. Among the clinical markers of treatment failure, physicians should consider no improvement in the ratio of arterial oxygen partial pressure to fractional inspired oxygen (PaO2/FiO2), persistence of fever or hypothermia, persistence of purulent respiratory secretions, and new-onset septic shock or multiple-organ dysfunction syndrome. Microbiological isolation of a new pathogen on day 3 is also associated with higher mortality, but persistence of the original pathogen does not seem to be associated with a worse prognosis. The real impact of changes to treatment after diagnosing nonresponsive VAP is unknown. Physicians must evaluate whether treatments are adequate in terms of sensitivity, dose, and route. Pharmacokinetically and pharmacodynamically optimized doses are recommended in these patients. Clinical stabilization of comorbidities or underlying conditions may be of benefit.
Keywords: ventilator-associated pneumonia; nonresponding pneumonia; mortality; microbiologic assessment; clinical response